Mitigation of performance variability induced by Checkpoint-Restart using DVFS - Κοκόλης, Απόστολος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ηλεκτρολόγων Μηχανικών και Μηχανικών Υπολογιστών. Τομέας Τεχνολογίας Πληροφορικής και Υπολογιστών, 2015)
As performance enhancement is accompanied by the aggressive integration of many-cores to a single chip and technology nodes approach deca-nanometer dimensions, the system's failure rate is becoming signi cant. Inevitably, computer systems must tolerate such failures. Both hardware and software methods are available enabling fault-tolerance to the systems. The Checkpoint/Restart technique provides reliability to the execution of an application. However, Checkpoint/Restart introduce an additional time overhead in order to achieve the fault-tolerance of the execution, that leads to performance variability. The scope of this thesis is to enhance a runtime manager, Depman, that orchestrates an application level Checkpoint/Restart technique so that such time overheads are absorbed, achieving performance predictability and reliability on the y, by using Dynamic Voltage and Frequency Scaling (DVFS). A closed-loop implementation controlling the clock frequency is proposed, that quanti es the time overheads induced by the checkpoint restart process and adjusts the frequency levels of the CPU so that execution time converges to the normal. Depman was also modi ed to extend its portability to other platforms and applications and was tested using the self fault injection module to both the Intel's Single-Chip Cloud Computer (SCC) and an x86 general computing platform, evaluating both the execution time and energy consumption of our scheme.